NaOH + HCl = NaCl + H2O
Na(+) + OH(-) + H(+) + Cl(-) = Na(+) + Cl(-) + H2O
H(+) + OH(-) = H2O
2NaOH + CO2 = Na2CO3 + H2O
2Na(+) + 2OH(-) + CO2 = 2Na(+) + CO3(-2) + H2O
2OH(-) + CO2 = CO3(-2) + H2O
2NaOH + CuCl2 = 2NaCl + Cu(OH)2
2Na(+) + 2OH(-) + Cu(+2) + 2Cl(-) = 2Na(+) + 2Cl(-) + Cu(OH)2
Cu(+2) + 2OH(-) = Cu(OH)2
2NaOH + ZnO +2H2O = Na2[Zn(OH)4] + H2
2Na(+) + 2OH(-) + ZnO + 2H2O = 2Na(+) + [Zn(OH)4](-2) + H2
2OH(-) + ZnO + 2H2O = [Zn(OH)4] (-2) + H2
Zn(OH)2 + 2NaOH = Na2[Zn(OH)4]
Zn(OH)2 + 2Na(+) + 2OH(-) = 2Na(+) + [Zn(OH)4](-2)
Zn(OH)2 + 2OH(-) = [Zn(OH)4](-2)
Объяснение:
1) 2Na3PO4 + 3CaBr2 =6 NaBr + Ca3(PO4)2
6Na(+) + 2PO4(3-) + 3Ca(2+) + 6Br(-) = 6Na(+) + 6Br(-) + Ca3(PO4)2
3Ca(2+)+ 2PO4(3-) = Ca3(PO4)2
K2SO3 + Ba(OH)2 = BaSO3 + 2KOH
2K(+) + SO3(2-) + Ba(2=) + 2OH(-) = BaSO3 + 2K(+) + 2OH(-)
Ba(2+) + SO3(2-) = BaSO3
2HNO3 + Na2SiO3 = 2NaNO3 + H2SiO3
2H(+) + 2NO3(-) + 2Na(+) + SiO3(2-) = 2Na(+) + 2NO3(-) + H2SiO3
2H(+) + SiO3(2-)= H2SiO3
2) Cu(OH)2 + 2HCl = CuCl2 + 2H2O
Cu(OH)2 + 2H(+) + 2Cl(-) = Cu(2=) + 2Cl(-)+ 2H2O
BaSO3 + 2HCl = BaCl2 + SO2 + H2O
BaSO3 + 2H(+) + 2Cl(-) = Ba(2+) +2Cl(-) + H2O